Rapid non-genomic activation of cytosolic cyclic AMP-dependent protein kinase activity and [Ca(2+)](i) by 17β-oestradiol in female rat distal colon - Doolan, Christina M (2000)
1. In this study, the effect of 17β-oestradiol on adenosine 3′ : 5′-cyclic monophosphate (cyclic AMP)-dependent protein kinase (PKA) activity was investigated. 2. Rapid (within 15 min) activation of basal PKA activity was observed in cytosolic fractions by 17β-oestradiol but not by 17α-oestradiol, progesterone or testosterone. This stimulation was abolished by the specific PKA inhibitor PKI but not by the classical oestrogen receptor antagonist tamoxifen. 3. 17β-Oestradiol did not stimulate basal PKA activity in membrane fractions or in cytosolic fractions from male rats. 4. The increase in cytosolic PKA activity was indirect as (i) it was inhibited by the adenylyl cyclase inhibitor SQ22536, (ii) it was mimicked by forskolin and (iii) 17β-oestradiol did not cause a stimulation of basal PKA activity in either type I or type II commercially available PKA holoenzymes. 5. Protein kinase Cδ (PKCδ) was directly activated by 17β-oestradiol. The specific PKC inhibitor, bisindolylmaleimide I (GF 109203X), abolished the 17β-oestradiol-induced PKA activation. 6. 17β-Oestradiol stimulated an increase in free intracellular calcium ion concentration ([Ca(2+)](i)) in isolated female but not male rat colonic crypts. This was inhibited by verapamil, nifedipine and zero extracellular [Ca(2+)] but unaffected by tamoxifen. 17α-Oestradiol, testosterone and progesterone failed to increase [Ca(2+)](i). 7. PKC and PKA inhibitors abolished the 17β-oestradiol-induced increase in [Ca(2+)](i). 8. These results demonstrate the existence of a novel 17β-oestradiol-specific PKA and Ca(2+) signalling pathway, which is both sex steroid- and gender-specific, in rat distal colonic epithelium.